(3GdaVGFd GdeLedI aj aVd GdHSedIs - (3YHO Gddg Hf Ydj Hf YHO GdQMef ShjOGf GdOedjLj,J (B1234 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde CeG HYO aGYdehG ENhGfi Cf HSe Gddg GdQMef GdQMje cdeI ef JMbb HgG adg LRjd GdfhGd s
(3BNQgG (B:s
(3adCLd PcQ Gdbdjd ef GdQMeI eG LhRJ GdEMQGb HGdfGQ , hGdQMef GdQMje GdPi de jJVQQ HLfGjGJ ef jMQb GdeDef GdPi OGhe Ydi TgGOI dG Edg EdG Gddg Sfjf hGddg JYGdi CYde HGdUhGH hEdjg GdeQLY hGdeBH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3HChdgG fbhd eNJdaIs
(3HgG fXGe GdJYbjHI JUhas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B89s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdeLGejYs